90.3k views
2 votes
m to the power of 5 ×m to the power of 6 × n to the power of 11 over m to the power of 3 × n to the power of 5 × n​

User Arbuthnott
by
6.3k points

2 Answers

0 votes

Answer:


(m^5 * m^6 * n^(11))/(m^3 * n^5 * n^1)

Explanation:

m to the power of 5 = m⁵

m to the power of 6 = m ⁶

n to the power of 3 = n³

n to the power of 11 = n¹¹


m^5 * m^6 * n^(11) over
m^3 * n^5 * n^1 =
(m^5 * m^6 * n^(11))/(m^3 * n^5 * n^1)

Simplified form:


m^((5+6-3)) * n^((11 - 5- 1)) = m^8 * n^(6)

User Paul Walczewski
by
6.3k points
2 votes

Explanation:


\frac{( {m}^(5) * {m}^(6) * {n}^(11))}{ {m}^(3) * {n}^(5) * n} \\ = \frac{ {m}^(11) * {n}^(11) }{ {m}^(3) * {n}^(6) } \\ = {m}^(8) * {n}^(5) \\ = {m}^(8) {n}^(5)

User Dermott
by
5.6k points